Advancing health equity in Nova Scotia by exploring gaps in healthcare delivery: a mixed methods protocol - Lane, Jennifer; Alizadeh, Neda; Cassidy, Christine; Forbes, Neil; McCulloch, Holly; Jarvis, Katrina; Wong, Helen; Pennell, Courtney; Wozney, Lori; Lane, Kris; Barber, Brittany; Lackie, Kelly; et al. (Research in Health Services & Regions, 2025)
Population health issues are addressed by various regional initiatives in the Canadian province of Nova Scotia (NS). A need for research on the root causes of health inequities suggests there may be a lack of evidence to inform current initiatives within the region. To address this gap, a three-phase sequential mixed methods study called Advancing Health Equity in NS by Exploring Gaps in Healthcare Delivery will operationalize Intersectionality Theory and employ an integrated knowledge translation approach to identify and explore gaps in health service delivery. This will promote a better understanding of how to improve the integration of health equity in health service and delivery systems and thus population health and well-being. The following objectives will be addressed in each phase: 1) create an inventory of NS-relevant knowledge that relates to health equity, 2) examine the integration of health equity in NS health service and delivery systems using a context-specific health equity lens, and 3) mobilize knowledge on how gaps in service delivery can be addressed to improve the integration of health equity and better meet the needs of people living in NS. The study results from this protocol will be used to integrate health equity in NS health service and delivery systems, enhancing the quality of care for populations rendered vulnerable by structural inequalities, and working to prevent negative impacts to health and wellbeing.